The influence of crystallization route on the SrBi2Nb2O9 thin films - Zanetti, S. M.; Leite, E. R.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Springer Nature, 1999)
Polycrystalline SrBi2Nb2O9-layered ferroelectric thin films were synthesized on Pt/Ti/SiO2/Si substrate using the polymeric precursors solution. The dip-coated films were specular and crack-free and crystallized during firing at 700 °C. Single-, double-, and triple-layered films were obtained by several dips in the deposition solution, and the influence of crystallization between each dip was studied. Microstructure and morphological evaluation were followed by grazing incident x-ray diffraction (GIXRD), scanning electron microscopy (SEM), and atomic force microscopy (AFM). Multilayered films obtained using the intermediate-crystallized layer route present a dense microstructure with spherical grains, with a preferential orientation in the 〈215〉 direction; films obtained using the intermediate-amorphous layer route are polycrystalline and present elongated grains around 250 nm in size.
Keywords: Crystal microstructure; Crystal orientation; Crystallization; Deposition; Ferroelectric materials; Grain size and shape; Morphology; Multilayers; Perovskite; Polycrystalline materials; Strontium compounds; Synthesis (chemical); Grazing incident X ray diffraction (GIXRD) analysis; Dielectric films